Low-cost mobile 3D scanning of heritage objects to facilitate long-distance research collaboration - a technical note - Dirk H.R. Spennemann; Sharnie Hurford (Journal of Digital Media & Interaction)
While three-dimensional visualization has become a common tool in various cultural heritage applications, the emphasis has been on high fidelity representation, essentially the generation of digital twins or digital reconstructions. Overlooked appears to be the utility of 3D in research collaboration where one of the researchers has access to the original, potentially fragile object while the others are based in remote locations. This paper describes the application of a low-cost, mobile and swiftly executable 3D scanning process and discusses the benefits of this for remote collaboration of three-dimensional objects of material culture.